ANALISIS WACANA KRITIS PEMBENTUKAN STEREOTIP PEMERINTAH OLEH HTI - Ali Kusno; Abd. Rahmad; Nur Bety (Fakultas Sastra Universitas Negeri Malang, 2017)
Abstract: This study aims to reveal the stereotypes about government formed by HTI in the propaganda bulletin articles published in Al-Islam. This study uses descriptive qualitative critical discourse analysis approach of Fairclough’s models. Based on textual analysis (micro analysis), discourse practical analysis and socio-cultural practical dimension (macro) the buletin indicates that HTI provides a solution by building a positive stigma against the struggle doctrine of HTI, namely the application of Islamic law and the need for Godly Muslim leaders. To reinforce the positive stigma about the ideology and the concept, HTI formed a variety of negative stereotypes of the Government by pointing at the Government’s inability, liberal economic system, capitalist government partisanship, transactional politics and the Government’s partisanship to foreign advantages. The formation of the various stereotypes may result in public antipathy towards the GovernmentPermalink/DOI: dx.doi.org/10.17977/um015v45i22017p143